Pelatihan Penggunaan Fungsi dan Formula Menggunakan Microsoft Excel Untuk Guru-Guru Pada SMP Swasta Citra Harapan - Silvia Lestari; Dani Manesah; Suryanto Suryanto; Darwatan Derajat (Lembaga Pengembangan Kinerja Dosen, 2024)
This training aims to enhance teachers' technical skills in using Microsoft Excel, particularly in managing academic and administrative data. The training covers the use of basic and advanced functions, chart creation, and data analysis. Evaluation results indicate a significant improvement in teachers' abilities, impacting the efficiency and effectiveness of school task management. The training also boosts teachers' confidence in using technology. Recommendations for further training and additional support are proposed to ensure the continuous improvement of teachers' skills in using Microsoft Excel.